Studi Korelasional Keaktifan dan Hasil Belajar Fisika dalam Implementasi Problem Based Learning pada Siswa Kelas XI IPA MAN 1 Mataram: - - Atika Wahyuni; Joni Rokhmat; I Wayan Gunada (Postgraduate Program, University of Mataram, 2026)
This study aims to (1) describe the level of student learning activity, (2) describe the level of student physics learning outcomes, and (3) analyze the relationship between learning activity and physics learning outcomes in the implementation of Problem-Based Learning (PBL). This research employed a correlational design with a quantitative approach. The population consisted of all 168 students in the eleventh-grade science classes, and a saturated sampling technique was used so that the entire population become the sample. Descriptive analysis was used to determine the levels of student learning activity and physics learning outcomes. For hypothesis testing, non-parametric statistics (Spearman correlation) were used because the data were not normally distributed. The results showed that (1) the level of student learning activity was 20,8% high, 49,4% medium, and 29,8% low; (2) the level of student physics learning outcomes was 1,2% high, 83,9% medium, and 14,9% low; (3) the Spearman correlation test revealed a significant positive correlation between the two variables (sig. 2-tailed = 0,003 < 0,05) with a low correlation level (correlation coefficient = 0,226). Based on the coefficient of determination, the contribution of learning activity to physics learning outcomes was only 5,1%. Thus, it can be concluded that there is a significant positive relationship between learning activity and physics learning outcomes, although this relationship is low and contributes only slightly.